Reciprocal relationships between parental and scholastic homework assistance and students’ academic functioning at elementary school - Benckwitz, Lisa; Kohl, Katharina; Roloff, Janina; Lüdtke, Oliver; Guill, Karin (Frontiers in Psychology, 2023)
Homework assistance is provided both by parents and by institutions, for example, full-day schools. Previous research found evidence that the quality of homework assistance – measured by three dimensions derived from the self-determination theory, namely, responsiveness, structure, and control – is reciprocally related with students’ academic functioning (i.e., achievement and homework behavior). However, findings on parental homework assistance have been consistent only for the secondary level, whereas elementary school students have been studied less and previous results obtained for this population are inconclusive. Moreover, research on homework assistance that is given at school is scarce. Therefore, the present study aimed to investigate whether reciprocal associations between the quality of homework assistance and students’ academic functioning in elementary school can be found (1) for parental homework assistance and (2) for scholastic homework assistance. We calculated cross-lagged panel models based on longitudinal data from 335 German fourth graders collected in autumn 2019 (September and October) and winter 2020 (February and March). The analyses for scholastic homework assistance were based on a subsample of 112 students. Whereas responsiveness and structure did not predict students’ outcomes in the way we expected, control had unfavorable relationships in both homework settings. Moreover, parental control was reciprocally related with students’ mean grades in three subjects. The positive forms of homework assistance (responsiveness and structure) were predicted by different indicators of academic functioning in the two homework settings.